462 VII Steady Oseen Fl ow in Exterior Domains
Ψ
2k
(ξ), with β = 1/2 , and for ξ
`
Ψ
2k
(ξ), with β = 0, k = 1, 2. As a consequence,
arguing exactly as in the proof of Theorem VII.4.1, we obtain (VII.5.3) with
a constant c independent of ε. Let us next show
u
ε
∈ W
1,q
(R
2
). (VII.5.5)
By Lemma VII.4.1, it suffices to prove, for some C = C(ε, R) and all `, m, k =
1, 2
|ξ
κ
1
1
| |ξ
κ
2
2
|
∂
κ
Ψ
mk
∂ξ
κ
1
1
∂ξ
κ
2
2
≤ C
|ξ
κ
1
1
| |ξ
κ
2
2
|
∂
κ
(ξ
`
Ψ
mk
)
∂ξ
κ
1
1
∂ξ
κ
2
2
≤ C
with κ
1
, κ
2
= 0, 1 and κ
1
+ κ
2
= κ. We now have, wi th c = c(κ
1
, κ
2
),
|ξ
κ
1
1
| |ξ
κ
2
2
|
∂
κ
Ψ
mk
∂ξ
κ
1
1
∂ξ
κ
2
2
≤ c
1
ξ
2
+ εR + |ξ
1
|
≤
c
εR
and
|ξ
κ
1
1
| |ξ
κ
2
2
|
∂
κ
(ξ
`
Ψ
mk
)
∂ξ
κ
1
1
∂ξ
κ
2
2
≤ c
|ξ|
ξ
2
+ εR + |ξ
1
|
≤
c
(εR)
1/2
and (VII.5 .5) follows. Finally, let w, τ satisfy conditio ns (a) and (b) stated in
the lemma and set v = w −u
ε
, p = τ −π
ε
. We then obtain that v obeys the
identity
(∇v, ∇ϕ) −R(v,
∂ϕ
∂x
1
) + ε(v, ϕ) = 0, for all ϕ ∈ D(Ω). (VII. 5.6)
However, by embedding Theorem II.3.2 , it follows that u
ε
∈ W
1,2
(R
2
) and
since ∇ · v = 0 we conclude v ∈ H
1
(R
2
). By continuity, we may then extend
identity (VII.5.6) to all ϕ ∈ H
1
(R
2
) and, in particular, we may take ϕ = v
to deduce
(∇v, ∇v) + ε(v, v) = R(v,
∂v
∂x
1
). (VII.5.7)
Since
(v,
∂v
∂x
1
) = 0,
(VII.5.7 ) yields v = 0 a.e. in R
2
and, consequently, from (b) and the a nalog ous
identity written for u
ε
, we have
(p, ∇ · ψ) = 0, for all ψ ∈ C
∞
0
(R
2
),
implying τ = π
ε
+ const a.e. in R
2
. The pro of of the lemma is therefore
complete. ut